Examination of the action of the iliocapsularis: Focusing on changes in shear elastic modulus owing to muscle elongation - Hikari Itsuda; Masahide Yagi; Hiroshige Tateuchi; Momoka Tokoro; Noriaki Ichihashi (PLoS ONE, 2025)
The iliocapsularis (IC) muscle contributes to hip stability and understanding its function in vivo is important. A previous study investigated the functional role of the IC by using electromyography. However, muscle can activate during not only their primary action, which is the direction to the moment arm, but also the stabilizers and fixators. As a result, clarifying the action of the muscle by measuring electromyography alone is a challenge. This study aimed to examine the action, namely the direction of the moment arm, of the IC using shear wave elastography. In total, 23 young healthy individuals (8 men and 15 women) participated in the study. The shear elastic modulus (G) of the right IC was measured in the following positions: (1) resting (hip flexion 0º, addiction 0º, and external rotation 0º), (2) hip flexion at 15º, (3) hip extension at 15º, (4) hip abduction at 15º, (5) hip adduction at 15º, (6) hip external rotation at 15º, and (7) hip internal rotation at 15º. Higher G values correspond to increased muscle elongation, assuming that the muscle acts in the opposite direction of the elevated G. Wilcoxon signed-rank test with Holm correction was performed to compare G between the resting position and each subsequent posture and between hip flexion–extension, hip abduction–adduction, and hip external–internal rotation. As a result, the G in extension (p < 0.001) and external rotation (p = 0.021) were significantly higher than that in the resting position. G in extension was higher than in flexion (p < 0.001), and G in external rotation was higher than in internal rotation (p = 0.007). These findings suggest that the IC is involved in hip flexion and internal rotation.